ANALISIS PENGEMBANGAN DIRI PADA KOMPETENSI PEDAGOGIK GURU SMA MODEL DI KOTA PALEMBANG - Dian Eka Amrina; edutivia Mardetini (Pendidikan Ekonomi FKIP Universitas Sriwijaya, 2019)
Abstract This study aims to describe the development of self in pedagogical competencies carried out by economic subject teachers as well as supporting and inhibiting factors in developing themselves in the SMA Kota Palembang Model. This study uses a qualitative approach with a case study method. The research subjects were determined using purposive sampling so that three teachers were certified on economic subjects at SMAN 4 Palembang. Data collection techniques used are interviews, and documentation. The data analysis technique uses the Miles and Huberman models. Self-development in the pedagogical competence of the teacher is still focused on the intensive activities held by the school, and has not touched cooperative and independent activities. Supporting factors for self-development are the opportunities provided by Palembang N 4 High School to develop themselves. While the inhibiting factor is the lack of participation from the government for self-development activities and lack of motivation from educators to develop self-competence through independent activities. Abstrak Penelitian ini bertujuan mendeskripsikan pengembangan diri pada kompetensi pedagogik yang dilakukan guru mata pelajaran ekonomi serta faktor pendukung dan penghambat dalam mengembangkan diri di SMA Model Kota Palembang. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Subjek penelitian di tentukan menggunakan purposive sampling sehingga diperoleh tiga guru yang tersertifikasi pada mata pelajaran ekonomi di SMAN 4 Palembang. Teknik pengumpulan data yang digunakan yaitu wawancara, dan dokumentasi. Teknik analisis data menggunakan model Miles dan Huberman. Pengembangan diri pada kompetensi pedagogik guru masih terfokus pada kegiatan intensif yang diadakan sekolah, dan belum menyentuh kegiatan kooperatif dan mandiri. Faktor pendukung pengembangan diri adalah kesempatan yang diberikan SMA N 4 Palembang untuk mengembangkan diri. Sedangkan faktor penghambatnya adalah kurangnya peran serta dari pemerintah untuk kegiatan pengembangan diri dan kurangnya motivasi dari pendidik untuk menumbuhkembangkan kompetensi diri melalui kegiatan mandiri